2009
DOI: 10.1097/eja.0b013e32832a22c2
|View full text |Cite
|
Sign up to set email alerts
|

Acute memory phase of sevoflurane preconditioning is associated with sustained translocation of protein kinase C-α and ϵ, but not δ, in isolated guinea pig hearts

Abstract: The acute memory phase of sevoflurane preconditioning is limited to less than 60 min. Sustained translocation of PKC-alpha and epsilon, but not delta, correlates with this acute memory phase of sevoflurane preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The role of nPKC␦ is controversial, since both protective and detrimental roles have been described (370, 551, 759). Interestingly, an increase in intracellular Ca 2ϩ by itself can mediate ischemic preconditioning (568), and there is strong evidence that the protective effect is mediated by activation of the Ca 2ϩ -dependent cPKC␣ isozyme (78,333,440,617,817,893,908,923 FIGURE 13. Different subtypes of K ATP channels may synergistically interact to protect the heart against stress and ischemic insults.…”
Section: Mechanisms By Which K Atp Channels Protect Against Ischemic mentioning
confidence: 99%
“…The role of nPKC␦ is controversial, since both protective and detrimental roles have been described (370, 551, 759). Interestingly, an increase in intracellular Ca 2ϩ by itself can mediate ischemic preconditioning (568), and there is strong evidence that the protective effect is mediated by activation of the Ca 2ϩ -dependent cPKC␣ isozyme (78,333,440,617,817,893,908,923 FIGURE 13. Different subtypes of K ATP channels may synergistically interact to protect the heart against stress and ischemic insults.…”
Section: Mechanisms By Which K Atp Channels Protect Against Ischemic mentioning
confidence: 99%
“…GSK3β is inactivated by phosphatidylinositol 3-kinase (PI3K)/Akt pathway and extracellular signal-regulated kinase 1/2 (Cohen and Frame, 2001). Recent studies have found that the volatile anesthetics such as isoflurane and sevoflurane induce cardioprotection by preconditioning and postconditioning (Bouwman et al, 2010;Inamura et al, 2010;Inamura et al, 2009;Kaneda et al, 2008;Okusa et al, 2009;Weber et al, 2005). Pravdic et al demonstrated that isoflurane preconditioning delays MPTP opening using the tetramethyl-rhodamine ethyl ester (TMRE) technique in rat cardiomyocytes (Pravdic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Brief, intermittent episodes of ischemia and reperfusion at the onset of reperfusion after prolonged ischemia confer cardioprotection from reperfusion injury (ischemic postconditioning). Recent studies show that this effect can be induced by brief administration of volatile anesthetics immediately before and after reperfusion, phenomena termed anesthetic preconditioning [1][2][3][4][5] and postconditioning [6,7]. The mechanisms responsible for anesthetic postconditioning remain unclear.…”
Section: Introductionmentioning
confidence: 99%